Protective film for preventing precipitation of small molecules and preparation method of protective film

By introducing functional layers and protective layers of barrier SiO2 and wear-resistant SiC nanowires into the protective film, the problem of insufficient barrier performance of existing protective films is solved, and efficient barrier against small molecule precipitation is achieved, while mechanical properties and transparency are improved.

CN120623545APending Publication Date: 2025-09-12TAIHU JINZHANG TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510739352.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The barrier properties of existing protective films are limited, making it difficult to effectively block the precipitation of small molecular substances such as oligomers and plasticizers. Existing methods often increase material thickness and cost, and reduce transparency and flexibility.

Method used

The functional layer and protective layer are composed of barrier SiO2 and wear-resistant SiC nanowires containing a fluoroaluminate inorganic interface layer and a polyetheramine organic interface layer. The vertical arrangement of SiO2 nanosheets and SiC nanowires is prepared using a mussel mucin template to form a structure similar to nacre and enamel, thereby enhancing the barrier and wear resistance.

Benefits of technology

Without affecting the mechanical properties, it significantly improves the barrier properties, prolongs the path of small molecule precipitation, enhances the bonding strength and wear resistance, and improves the transparency and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120623545A_ABST
    Figure CN120623545A_ABST
Patent Text Reader

Abstract

The invention discloses a protective film for preventing precipitation of small molecules and a preparation method thereof, and relates to the technical field of protective films. The protective film comprises a base material layer, a functional layer stacked on one side of the base material layer and a protective layer stacked on the functional layer; wherein the functional layer comprises barrier S O2 with a fluorine-containing aluminate inorganic interface layer and a polyether amine organic interface layer; the protective layer comprises wear-resistant S C of which the surface is grafted with amino methyl ester groups; the double-layer interface of the functional layer can enhance the barrier effect and is beneficial to preventing precipitation of small molecules; a perfluoro chain segment in the protective layer can enhance hydrophobicity, a good waterproof effect is achieved, and the influence of the external environment on the base material is further avoided; and the carbamate group on the surface of the wear-resistant S C and the benzoxazine ring of the barrier S O2 are subjected to ring-opening copolymerization at a high temperature to form a covalent cross-linking interface, so that the bonding strength can be enhanced, the tensile property can be improved, and the service life of the protective film can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective films, and in particular to a protective film for preventing small molecules from precipitating and a preparation method thereof. Background Art

[0002] During the production and use of protective films, substrates such as BOPP, BOPET, BOPA, PET, PE, PC, TAC, PP, PS, PMMA, TPU, PI, PVB, PVC, etc. may precipitate small molecules such as oligomers, plasticizers, antioxidants, etc. due to processing temperature, storage conditions or environmental factors. These precipitates may affect the appearance and performance of the product.

[0003] At present, most existing protective films use a single material or a simple coating structure, and their barrier properties are limited, making it difficult to meet high barrier requirements. In addition, the existing technology lacks a method for preparing a protective film that can effectively block the precipitation of small molecules while also having good mechanical properties, transparency, and processing performance.

[0004] First, the barrier properties of existing protective films are limited. When PET materials are exposed to high temperatures or prolonged use, small molecules such as oligomers and plasticizers are easily precipitated, affecting product performance and safety. Although barrier properties can be enhanced through multi-layer lamination or coating, these methods often increase material thickness and cost, and may reduce transparency and flexibility. Summary of the Invention

[0005] The purpose of the present invention is to provide a protective film for preventing small molecules from precipitating and a preparation method thereof, and to solve the following technical problems:

[0006] How to improve the barrier properties of the protective film without affecting its mechanical properties.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] In a first aspect, the present invention discloses a protective film for preventing small molecules from precipitating, comprising a substrate layer, a functional layer stacked on one side of the substrate layer, and a protective layer stacked on the functional layer;

[0009] The functional layer comprises barrier SiO2 having an inorganic interface layer containing fluorine-aluminate and an organic interface layer containing polyetheramine; and the protective layer comprises wear-resistant SiC with aminomethyl ester groups grafted on the surface.

[0010] Furthermore, the material of the substrate layer is BOPP, BO, BOPA, PE, PC, TAC, PP, PS, PMMA, TPU, PI, PVB, PVC, and / or

[0011] Preferably, the thickness of the substrate layer is 25-100 μm, more preferably 38 μm.

[0012] Preferably, the thickness of the functional layer is 0.01-1 μm, more preferably 1.0 μm.

[0013] Preferably, the thickness of the protective layer is 8-20 μm, more preferably 15 μm.

[0014] Furthermore, the preparation method of the barrier SiO2 comprises the following steps:

[0015] Step A1, dissolving mussel mucin at 1.5-2 wt% (preferably 1.8 wt%) in a citric acid buffer solution, stirring, cooling, and then standing to form a β-pleated fiber network to obtain a static solution; then forming a protein fiber membrane by electrospinning deposition, and then crushing the protein fiber membrane and adding 20-25 wt% (preferably 22 wt%) of the protein fiber membrane to a sodium silicate aqueous solution for mineralization to obtain a mineralized membrane;

[0016] Step A2, dissolving perfluorohexyl ethylaluminate in anhydrous ethanol to form a modification solution, placing the mineralized film in the modification solution, and stirring the reaction under a nitrogen atmosphere to obtain primary modified SiO2;

[0017] Step A3: adding polyetheramine and trifluoroethyl 3-mercaptopropionate to DMF at a molar ratio of 1:15, reacting at 60° C. for 12 h, dialysis purification, and freeze-drying to obtain thiolated HPEA, adding a photoinitiator to the thiolated HPEA, and then immersing the initially modified SiO2 in it, and UV curing under a nitrogen atmosphere for 1-2 h to obtain a barrier SiO2 precursor;

[0018] Step A4: placing the barrier SiO2 precursor in a tube furnace for gradient heat treatment to obtain barrier SiO2.

[0019] Preferably, in step A1, the pH of the citric acid buffer is 4.5.

[0020] Preferably, in step A1, the stirring and cooling followed by standing still conditions are: magnetic stirring at 600 rpm for 2 hours, followed by cooling to 4° C. and standing still for 12 hours.

[0021] Preferably, in step A1, the operation method for forming the protein fiber membrane by electrospinning deposition is: the static liquid is loaded into the injection pump, and a protein fiber membrane with a thickness of 45-55um (preferably 50um) is deposited on an aluminum foil collector at a flow rate of 0.5mL / min and a voltage of 12kV.

[0022] Preferably, in step A1, the protein fiber membrane is crushed and then added to a sodium silicate aqueous solution at 20-25wt% for mineralization. The operation method is as follows: the protein fiber membrane is placed in a crusher and crushed, and then added to a 5wt% sodium silicate aqueous solution at 20-25wt%, and the mineralization reaction is carried out at 4-6°C under 40kHz, 100W ultrasound for 6h, and finally the filtrate is filtered to remove the filtrate.

[0023] Preferably, in step A2, the preparation method of the perfluorohexyl ethyl aluminate is as follows: perfluorohexyl ethanol and aluminum triisopropoxide are uniformly mixed in a molar ratio of 2:1, and reacted at 130° C. for 8 hours to obtain the product.

[0024] Preferably, in step A2, the concentration of perfluorohexyl ethylaluminate in the modified solution is 0.2 mol / L.

[0025] Preferably, in step A2, the ratio of the mineralized membrane to the modified solution is 1 g: (5-8) mL; preferably 1 g: 6 mL

[0026] Preferably, in step A2, the stirring reaction is carried out at 120 rpm and 60° C. for 24 h.

[0027] Preferably, in step A3, the ratio of the total amount of the polyetheramine and trifluoroethyl 3-mercaptopropionate to the DMF solvent is 1 g:20 mL.

[0028] Preferably, in step A3, the photoinitiator is Irgacure 2959, and the amount of the photoinitiator added is 1-2 wt % of the thiol-HPEA.

[0029] Preferably, in step A3, the UV curing conditions are: wavelength 365nm, energy 10mW / cm 2 .

[0030] Based on this, a preferred method for preparing barrier SiO2 is obtained, comprising the following steps:

[0031] Step a1, dissolving mussel mucin at 1.8wt% in a citric acid buffer solution with a pH of 4.5, magnetically stirring at 600rpm for 2h, cooling to 4°C and standing for 12h to obtain a static solution; loading the static solution into a syringe pump, depositing a protein fiber membrane with a thickness of 50um on an aluminum foil collector at a flow rate of 0.5mL / min and a voltage of 12kV, placing the protein fiber membrane in a crusher and crushing it, adding 22wt% to a 5wt% sodium silicate aqueous solution, and mineralizing the reaction at 5°C under an ultrasonic wave of 40kHz and 100W for 6h, and finally filtering and removing the filtrate to obtain a mineralized membrane;

[0032] Step a2, perfluorohexylethanol and aluminum triisopropoxide were uniformly mixed in a molar ratio of 2:1, and the mixture was reacted at 130°C for 8 hours to obtain perfluorohexyl ethylaluminate; perfluorohexyl ethylaluminate was dissolved in anhydrous ethanol to form a modification solution with a concentration of 0.2 mol / L, and the mineralized film was placed in the modification solution at a dosage ratio of 1 g:6 mL, and the mixture was stirred at 120 rpm and 60°C under a nitrogen atmosphere for 24 hours to obtain primary modified SiO2;

[0033] Step a3, polyetheramine and trifluoroethyl 3-mercaptopropionate were added to DMF in a molar ratio of 1:15, and the total amount of polyetheramine and trifluoroethyl 3-mercaptopropionate to DMF solvent was 1 g:20 mL; the reaction was carried out at 60° C. for 12 h, and the mixture was dialyzed and purified, followed by freeze-drying to obtain thiolated HPEA. 1.5 wt% of Irgacure 2959 was added to the thiolated HPEA, and the primary modified SiO2 was immersed in the mixture. The mixture was subjected to ionization under a nitrogen atmosphere at a wavelength of 365 nm and an energy of 10 mW / cm 2 The film was cured under ultraviolet light for 1.5 h to obtain a barrier SiO2 precursor;

[0034] Step a4: Place the barrier SiO2 precursor in a tube furnace, first treat it at 120°C for 2 hours, then heat it to 180°C for 1 hour to obtain barrier SiO2.

[0035] Furthermore, the preparation method of the wear-resistant SiC comprises the following steps:

[0036] Step B1, dispersing SiC nanowires at 0.5 wt% in a supercritical CO2 / ethanol mixed solvent, ultrasonically treating the nanowires, performing plasma-assisted electrophoresis, and then performing vapor deposition with perfluorodecyltrimethoxysilane to obtain modified SiC;

[0037] Step B2: trimethylolpropane triglycidyl ether and boric acid-modified polysiloxane are mixed in a molar ratio of 4:1, and then 0.5 wt% of stannous octoate is added, and the mixture is reacted at 60° C. for 40 minutes to obtain a prepolymer, and then modified SiC is added for gradient temperature curing to obtain wear-resistant SiC.

[0038] Preferably, in step B1, the operation method of vapor deposition using perfluorodecyltrimethoxysilane is as follows: placing the SiC nanowires after plasma-assisted electrophoresis in a CVD furnace, introducing perfluorodecyltrimethoxysilane vapor at a rate of 0.5 L / min, reacting at 250° C. for 4 h, and then washing and drying.

[0039] Preferably, in step B2, the weight ratio of the prepolymer to the modified SiC nanowires is 1:(3-5), more preferably 1:4.

[0040] Based on this, a preferred method for preparing wear-resistant SiC is obtained, comprising the following steps:

[0041] Step b1, dispersing SiC nanowires at 0.5wt% in a supercritical CO2 / ethanol (supercritical CO2 / ethanol volume ratio of 1:4) mixed solvent, ultrasonically treating at 40kHz, 500W at 50°C, 13.8MPa for 1h to obtain a dispersion, then injecting the dispersion into a parallel electrode mold with a spacing of 1mm, applying an 8kV / cm electric field, and simultaneously turning on an argon plasma with a power of 300W and 13.56MHz for 30min, then placing it in a CVD furnace, passing perfluorodecyltrimethoxysilane vapor at a rate of 0.5L / min, reacting at 250°C for 4h, and then washing with hexamethyldisilazane (HMDS) and a fluorinated solvent (FC-40) three times in sequence. After washing, placing it in a drying oven at 80°C under vacuum for 2h to obtain modified SiC;

[0042] Step b2: trimethylolpropane triglycidyl ether and boric acid-modified polysiloxane are mixed in a molar ratio of 4:1, and then 0.5 wt% of stannous octoate is added, and the mixture is reacted at 60°C for 40 minutes to obtain a prepolymer, and then 4 times the amount of modified SiC as the prepolymer is added for gradient temperature curing to obtain wear-resistant SiC.

[0043] In a second aspect, the present invention further discloses a method for preparing the protective film for preventing small molecules from precipitating as described above, comprising the following steps:

[0044] Step 1: corona treating the substrate layer;

[0045] Step 2: dissolving barrier SiO2 and binder in a solvent at a weight ratio of 100:(2-5) and mixing them evenly, then coating them on the corona-treated substrate layer, and drying and curing them to form a functional layer;

[0046] Step 3: Dissolve the wear-resistant SiC and the antistatic agent in a solvent at a weight ratio of 100:(5-8) and mix them evenly, then apply them on the functional layer, dry and solidify them to form a protective layer, that is, obtain a protective film that prevents small molecules from precipitating.

[0047] Preferably, in step 1, the material of the substrate layer is BO, and its surface tension reaches above 50 mN / m after corona treatment.

[0048] Preferably, in step 2, the adhesive is polyurethane, epoxy resin, acrylic resin, and / or; more preferably polyurethane.

[0049] Preferably, in step 2, the solvent is ethyl acetate.

[0050] Preferably, in step 2, the ratio of the total amount of the barrier SiO2 and the binder to the solvent is 1 g:20 mL.

[0051] Preferably, in step three, the antistatic agent is a quaternary ammonium salt antistatic agent, an alkyl sulfonate antistatic agent, a polyether antistatic agent, and / or; more preferably a polyether antistatic agent.

[0052] Preferably, in step three, the solvent is ethyl acetate.

[0053] Preferably, in step three, the ratio of the total amount of the wear-resistant SiC and the antistatic agent to the solvent is 1 g:20 mL.

[0054] Based on this, a preferred method for preparing a protective film for preventing small molecules from precipitating is obtained, comprising the following steps:

[0055] Step 1: corona treat the 2 mm thick BO substrate layer to make its surface tension reach above 50 mN / m;

[0056] Step 2: Dissolve barrier SiO2 and binder in ethyl acetate at a weight ratio of 100:3 and mix evenly. The total amount of barrier SiO2 and binder to the solvent ratio is 1g:20mL. Then, apply the mixture on the corona-treated BO substrate layer and dry and solidify to form a functional layer.

[0057] Step 3: Dissolve the wear-resistant SiC and the antistatic agent in a solvent at a weight ratio of 100:6 and mix them evenly. The total amount of the wear-resistant SiC and the antistatic agent and the solvent is 1g:20mL. Then apply them on the functional layer, dry and solidify them to form a protective layer, that is, obtain a protective film that prevents the precipitation of small molecules.

[0058] Beneficial effects of the present invention:

[0059] 1. The protective film for preventing the precipitation of small molecules of the present invention adds a functional layer and a protective layer to the outside of the substrate layer, wherein barrier SiO2 is added to the functional layer. During the preparation process, a mussel byssus protein template is used to induce the vertical growth of silica nanosheets, forming a "brick-mud" structure similar to the nacre, thereby extending the penetration path of small molecules and improving the barrier effect. At the same time, a fluorine-containing aluminate is introduced by grafting perfluorohexyl ethylaluminate on the silanol group of SiO2 to form an inorganic interface layer, and then a thiol-containing polyetheramine is introduced on the inorganic interface layer to form an organic interface layer containing a benzoxazine ring at the end. The double-layer interface further enhances the barrier effect, which is beneficial to preventing the precipitation of small molecules.

[0060] 2. The protective film for preventing small molecule precipitation of the present invention adds a functional layer and a protective layer to the outside of the substrate layer. Among them, wear-resistant SiC is added to the protective layer. During the preparation process, the vertically arranged SiC nanowires can form a bundle structure similar to enamel after plasma treatment, thereby enhancing wear resistance; the introduction of perfluorodecyltrimethoxysilane makes the ends of the SiC nanowires connected with perfluorinated chain segments, thereby enhancing their hydrophobicity, achieving a good waterproof effect, and further preventing the influence of the external environment on the substrate.

[0061] 3. The protective film for preventing small molecules from precipitating of the present invention adds a functional layer and a protective layer to the outside of the substrate layer. When the protective layer is prepared on the functional layer, the carbamate group (-NHCOO-) on the surface of the wear-resistant SiC and the benzoxazine ring of the barrier SiO2 undergo ring-opening copolymerization at high temperature to form a covalent cross-linked interface, which can enhance the bonding strength and form an integrated barrier interface. At the same time, the perfluorinated chain segment at the end of the SiC nanowire will be inserted into the gap of the Al-O layer of the barrier SiO2, forming a molecular-level hook effect, further enhancing its bonding strength, thereby enhancing the barrier effect against small molecule precipitation. At the same time, the enhancement of the bonding strength also further achieves the improvement of the tensile properties, thereby extending the service life of the protective film. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a product picture of the protective film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0063] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0064] Unless otherwise specified, the experimental methods in the following preparations, examples, and comparative examples are conventional methods and were performed according to the techniques or conditions described in literature in the field or according to product specifications. The materials and reagents used in the following examples were all commercially available unless otherwise specified.

[0065] Preparation Example 1

[0066] Preparation of barrier SiO2;

[0067] Step 1, dissolving mussel mucin at 1.8wt% in a citric acid buffer solution with a pH of 4.5, magnetically stirring at 600rpm for 2h, cooling to 4°C and standing for 12h to obtain a static solution; loading the static solution into a syringe pump, depositing a protein fiber membrane with a thickness of 50um on an aluminum foil collector at a flow rate of 0.5mL / min and a voltage of 12kV, placing the protein fiber membrane in a crusher and crushing it, adding 22wt% to a 5wt% sodium silicate aqueous solution, and mineralizing the reaction at 5°C under an ultrasonic wave of 40kHz and 100W for 6h, and finally filtering and removing the filtrate to obtain a mineralized membrane;

[0068] Step 2: Perfluorohexylethanol and aluminum triisopropoxide were uniformly mixed in a molar ratio of 2:1, and the mixture was reacted at 130°C for 8 hours to obtain perfluorohexyl ethylaluminate; perfluorohexyl ethylaluminate was dissolved in anhydrous ethanol to form a modification solution with a concentration of 0.2 mol / L, and the mineralized film was placed in the modification solution at a dosage ratio of 1 g:6 mL, and the mixture was stirred at 120 rpm and 60°C under a nitrogen atmosphere for 24 hours to obtain primary modified SiO2;

[0069] Step 3: Add polyetheramine and trifluoroethyl 3-mercaptopropionate to DMF at a molar ratio of 1:15, and the total amount of polyetheramine and trifluoroethyl 3-mercaptopropionate to the DMF solvent is 1 g:20 mL; react at 60° C. for 12 h, dialyze and purify, and then freeze-dry to obtain thiolated HPEA. 1.5 wt% of Irgacure 2959 is added to the thiolated HPEA, and the primary modified SiO2 is immersed in it. The reaction is carried out under a nitrogen atmosphere at a wavelength of 365 nm and an energy of 10 mW / cm 2 The film was cured under ultraviolet light for 1.5 h to obtain a barrier SiO2 precursor;

[0070] Step 4: Place the barrier SiO2 precursor in a tube furnace, first treat it at 120°C for 2 hours, then heat it to 180°C for 1 hour to obtain barrier SiO2.

[0071] Preparation Example 2

[0072] Preparation of wear-resistant SiC:

[0073] Step 1: Disperse SiC nanowires at 0.5 wt% in a supercritical CO2 / ethanol (supercritical CO2 / ethanol volume ratio is 1:4) mixed solvent, and ultrasonically treat at 40 kHz and 500 W for 1 h at 50 ° C and 13.8 MPa to obtain a dispersion. The dispersion is then injected into a parallel electrode mold with a spacing of 1 mm, an 8 kV / cm electric field is applied, and an argon plasma with a power of 300 W and 13.56 MHz is simultaneously turned on for 30 min. Then, the dispersion is placed in a CVD furnace and perfluorodecyltrimethoxysilane vapor is introduced at a rate of 0.5 L / min. The mixture is reacted at 250 ° C for 4 h, and then washed three times with hexamethyldisilazane (HMDS) and a fluorinated solvent (FC-40). After washing, the mixture is placed in a drying oven and vacuum dried at 80 ° C for 2 h to obtain modified SiC;

[0074] Step 2: Trimethylolpropane triglycidyl ether and boric acid-modified polysiloxane are mixed in a molar ratio of 4:1, and then 0.5 wt% of stannous octoate is added. The mixture is reacted at 60°C for 40 minutes to obtain a prepolymer. Then, 4 times the amount of modified SiC as the prepolymer is added for gradient temperature curing to obtain wear-resistant SiC.

[0075] Example 1

[0076] Preparation of protective film:

[0077] Step 1: Place the BO substrate layer with a thickness of 38 μm in a corona treatment machine for corona treatment to make its surface tension reach 55 mN / m;

[0078] Step 2: The barrier SiO2 and polyurethane prepared in Preparation Example 1 were dissolved in ethyl acetate at a weight ratio of 100:3 and mixed evenly. The total amount of barrier SiO2 and binder to the solvent was 1 g:20 mL. The mixture was then spray-coated on the BO substrate layer to a thickness of 1 μm. The mixture was placed in a drying oven and dried and cured at 100°C for 2 minutes to form a functional layer.

[0079] Step 3: The wear-resistant SiC and the quaternary ammonium antistatic agent of Preparation Example 2 were dissolved in ethyl acetate in a weight ratio of 100:6 and mixed evenly. The total amount of the wear-resistant SiC and the quaternary ammonium antistatic agent and the solvent were used in a ratio of 1g:20mL. The functional layer was then coated with a spray gun to a coating thickness of 15um. The coating was placed in a drying oven and dried and cured at 130°C for 2min to form a protective layer. Figure 1 The protective film shown prevents the precipitation of small molecules.

[0080] Example 2

[0081] Preparation of protective film:

[0082] Compared with Example 1, the only difference is that in step 2, the weight ratio of barrier SiO2 and polyurethane is 100:2; in step 3, the weight ratio of wear-resistant SiC and quaternary ammonium salt antistatic agent is 100:5; and finally a protective film that prevents the precipitation of small molecules is obtained.

[0083] Example 3

[0084] Preparation of protective film:

[0085] Compared with Example 1, the only difference is that in step 2, the weight ratio of barrier SiO2 and polyurethane is 100:5; in step 3, the weight ratio of wear-resistant SiC and quaternary ammonium salt antistatic agent is 100:8; and finally a protective film that prevents the precipitation of small molecules is obtained.

[0086] Comparative Example 1

[0087] Preparation of protective film:

[0088] Compared with Example 1, the only difference is that in step 2, the barrier SiO2 is replaced by polyurethane; the other steps and conditions remain the same, and a protective film is finally prepared.

[0089] Comparative Example 2

[0090] Preparation of protective film:

[0091] Compared with Example 1, the only difference is that in step 3, the wear-resistant SiC is replaced by a quaternary ammonium salt antistatic agent; the other steps and conditions remain the same, and a protective film is finally prepared.

[0092] Comparative Example 3

[0093] Compared with Example 1, the only difference is that: in step 2, the barrier SiO2 is replaced by polyurethane; in step 3, the wear-resistant SiC is replaced by a quaternary ammonium salt antistatic agent; the other steps and conditions remain the same, and a protective film is finally obtained.

[0094] The protective films prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, including acetaldehyde rejection, oligomer rejection, light transmittance, and tensile strength. The test methods were as follows:

[0095] Acetaldehyde rejection rate: gas chromatography-mass spectrometry (GC-MS)

[0096] 1. Cut the material to be tested into a 5*5cm test sample; 2. Secure the sample in the middle of the permeation cell, separating the high-concentration side (acetaldehyde source) from the low-concentration side (carrier gas side); 3. Use an inert gasket at the seal to prevent leakage; 4. Introduce acetaldehyde standard gas into the high-concentration side and carrier gas (N2) into the low-concentration side, with a flow rate of 10-50mL / min; 5. First, pass the carrier gas for 30 minutes to remove air, then introduce acetaldehyde gas; 6. Inject the low-concentration gas directly into the GC through a six-way valve; 7. Inject the sample with acetaldehyde standard gas and record the peak area; draw a concentration-peak area standard curve, record the data, and perform calculations;

[0097] Oligomer rejection: Gas chromatography-mass spectrometry (GC-MS)

[0098] 1. Take a sample and cut it into 5x5cm test pieces, ensuring the surface is clean. 2. Heat the cut sample in a 105°C oven for 24 hours. 3. Expose one side of the sample to oligomer vapor (e.g., siloxane saturated gas) while the other side is exposed to inert gas (N2) to carry the permeate. The permeate is adsorbed through a Tenax tube, thermally desorbed, and then fed into a GC-MS. 4. Quantify using a standard curve method, record the data, and calculate.

[0099] Light transmittance: Light transmittance haze meter

[0100] 1. Take a sample and cut it into a 5*5cm test specimen. 2. Turn on the transmittance haze meter and preheat it for 15-30 minutes. Click "Standard Calibration" on the display. Wait until TT shows "100" and HAZE shows "0.00" to start the test. 3. Remove the release film from the test specimen and place it in the tester's light incident channel, with the adhesive side facing the light incident and close the instrument door. 4. Press the "Measure" button to read and record the test results. The data displayed below HAZE is the haze value (test conditions are visible light with a wavelength of 380-780).

[0101] Tensile strength: tensile testing machine

[0102] 1. Cut the spline into length and width: 8CM*1CM spline, and mark 1CM length vertically in the middle of the spline. Tear off the light release surface, and stick 100PET on both ends, leaving a space for the marked 1CM width.

[0103] 2. First, clamp the upper clamp to ensure that the spline is vertical, plug the extra bent part of the spline into the lower clamp, and then clamp the lower clamp; 3. Reset and test until the material breaks, record the maximum force, tensile length, and calculate.

[0104] The test results are listed in Table 1, which is as follows:

[0105] Table 1

[0106]

[0107] By analyzing the data in Table 1, it can be seen that compared with Comparative Examples 1-3, the protective films prepared in Examples 1-3 have stronger barrier properties and better tensile properties for acetaldehyde and oligomers, and can meet the high barrier rate for small molecules while achieving excellent mechanical effects.

[0108] The above is a detailed description of an embodiment of the present invention. However, the content described is only a preferred embodiment of the present invention and should not be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A protective film for preventing small molecules from precipitating, characterized in that: It includes a base material layer, a functional layer stacked on one side of the base material layer, and a protective layer stacked on the functional layer; The functional layer comprises barrier SiO2 having an inorganic interface layer containing fluorine-aluminate and an organic interface layer containing polyetheramine; and the protective layer comprises wear-resistant SiC with aminomethyl ester groups grafted on the surface.

2. The protective film for preventing small molecules from precipitating according to claim 1, characterized in that: The material of the substrate layer is BOPP, BO, BOPA, PE, PC, TAC, PP, PS, PMMA, TPU, PI, PVB, PVC, and / or.

3. The protective film for preventing small molecules from precipitating according to claim 1, characterized in that: The preparation method of the barrier SiO2 comprises the following steps: Step A1, dissolving mussel mucin in a citric acid buffer at 1.5-2 wt%, stirring, cooling, and then standing, and then depositing by electrospinning to form a protein fiber membrane, and then crushing the protein fiber membrane and adding 20-25 wt% of sodium silicate aqueous solution for mineralization to obtain a mineralized membrane; Step A2, dissolving perfluorohexyl ethylaluminate in anhydrous ethanol to form a modification solution, placing the mineralized film in the modification solution, and stirring the reaction under a nitrogen atmosphere to obtain primary modified SiO2; Step A3: adding polyetheramine and trifluoroethyl 3-mercaptopropionate to DMF at a molar ratio of 1:15, reacting at 60° C. for 12 h, dialysis purification, and freeze-drying to obtain thiolated HPEA, adding a photoinitiator to the thiolated HPEA, and then immersing the initially modified SiO2 in it, and UV curing under a nitrogen atmosphere for 1-2 h to obtain a barrier SiO2 precursor; Step A4: placing the barrier SiO2 precursor in a tube furnace for gradient heat treatment to obtain barrier SiO2.

4. The protective film for preventing small molecules from precipitating according to claim 3, characterized in that: In step A1, the protein fiber membrane is crushed and then added to a sodium silicate aqueous solution at 20-25wt% for mineralization. The operation method is as follows: the protein fiber membrane is placed in a crusher and crushed, and then 20-25wt% is added to a 5wt% sodium silicate aqueous solution. The mineralization reaction is carried out at 4-6°C under 40kHz, 100W ultrasound for 6 hours, and finally the filtrate is filtered to remove the filtrate.

5. The protective film for preventing small molecules from precipitating according to claim 3, characterized in that: In step A2, the preparation method of the perfluorohexyl ethyl aluminate is as follows: perfluorohexyl ethanol and aluminum triisopropoxide are uniformly mixed in a molar ratio of 2:1, and reacted at 130° C. for 8 hours to obtain the product.

6. The protective film for preventing small molecules from precipitating according to claim 3, characterized in that: In step A2, the concentration of perfluorohexyl ethylaluminate in the modifying solution is 0.2 mol / L; the usage ratio of the mineralized membrane to the modifying solution is 1 g:(5-8) mL.

7. The protective film for preventing small molecules from precipitating according to claim 1, characterized in that: The preparation method of the wear-resistant SiC comprises the following steps: Step B1, dispersing SiC nanowires at 0.5 wt% in a supercritical CO2 / ethanol mixed solvent, ultrasonically treating the nanowires, performing plasma-assisted electrophoresis, and then performing vapor deposition with perfluorodecyltrimethoxysilane to obtain modified SiC; Step B2: trimethylolpropane triglycidyl ether and boric acid-modified polysiloxane are mixed in a molar ratio of 4:1, and then 0.5 wt% of stannous octoate is added, and the mixture is reacted at 60° C. for 40 minutes to obtain a prepolymer, and then modified SiC is added and cured by gradient temperature increase to obtain wear-resistant SiC.

8. The protective film for preventing small molecules from precipitating according to claim 7, characterized in that: In step B1, the operation method for vapor deposition using perfluorodecyltrimethoxysilane is as follows: the SiC nanowires after plasma-assisted electrophoresis are placed in a CVD furnace, perfluorodecyltrimethoxysilane vapor is introduced at a rate of 0.5 L / min, the reaction is carried out at 250° C. for 4 hours, and then the reaction is carried out by washing and drying.

9. The protective film for preventing small molecules from precipitating according to claim 7, characterized in that: In step B2, the weight ratio of the prepolymer to the modified SiC nanowires is 1:(3-5).

10. A method for preparing a protective film for preventing small molecules from precipitating according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: corona treating the substrate layer; Step 2: dissolving barrier SiO2 and binder in a solvent at a weight ratio of 100:(2-5) and mixing them evenly, then coating them on the corona-treated substrate layer, and drying and curing them to form a functional layer; Step 3: Dissolve the wear-resistant SiC and the antistatic agent in a solvent at a weight ratio of 100:(5-8) and mix them evenly, then apply them on the functional layer, dry and solidify them to form a protective layer, that is, obtain a protective film that prevents small molecules from precipitating.

Citation Information

Cited By

  • Intrinsic anti-static polarizer protective film base film and preparation method thereof

    CN121537664A